2020
DOI: 10.3934/jimo.2018144
|View full text |Cite
|
Sign up to set email alerts
|

Application of preservation technology for lifetime dependent products in an integrated production system

Abstract: It is important to adopt precisely the optimum level of preservation technology for deteriorating products, as with every passing day, a larger number of items deteriorate and cause an economic loss. For earning more profit, industries have a tendency to add more preservatives for long lifetime of products. However, realizing the health issues, there is a boundary that no manufacturer can add huge amount of preservatives for infinite lifetime of products. The correlation between the long lifetime along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Qin et al [40] suggested that the rate of deterioration increases with temperature as well as time. Iqbal and Sarkar [41] and Iqbal and Sarkar [42] suggested that the rate deterioration depends on the products' lifetime which is controllable.…”
Section: Product Deteriorationmentioning
confidence: 99%
“…Qin et al [40] suggested that the rate of deterioration increases with temperature as well as time. Iqbal and Sarkar [41] and Iqbal and Sarkar [42] suggested that the rate deterioration depends on the products' lifetime which is controllable.…”
Section: Product Deteriorationmentioning
confidence: 99%
“…As per the government legislation, to protect the human and environment, disposal of wastes generated from industries, electronic items, and hospitals by considering proper DC to reduce environmental harms (Lee et al, 2004). To manage the environmental sustainability, the items that cannot be preserved by adding preservatives anymore, are disposed of with proper protection (Iqbal and Sarkar, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%